Analisis Partisipasi Masyarakat dan Pemerintah dalam Pengembangan Sektor Pariwisata Kabupaten Bone, Sulawesi Selatan - Andi Hasbi; Muh. Zainuddin Badollahi (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2019)
The tourism sector is indeed quite promising to help increase foreign exchange reserves and pragmatically also able to increase people's incomes, sustainable tourism development is defined as a tourism development process oriented to the preservation of resources needed for future development where the surrounding community acts as a provider of tourist needs services. Humanitarian factors and local cultural entities should not be ignored, meaning that community life should not be uprooted from its cultural roots only because of the commercial emphasis of tourism, the lifestyle and culture of local communities, so researchers want to see how the role of community and government participation in development tourism as a leading destination and how tourism development is realized as a superior destination.